Unified ultraviolet communication and sensing:modeling and system optimization - Chen GONG; Yuchen PAN; Zhengyuan XU (Tongxin xuebao)
Currently, there exist few communication works which combine with sensing.It is necessary to build up a unified communication and sensing signal model and system joint design optimization framework.Based on this, a unified ultraviolet communication and sensing framework was proposed, consisting of a transmitter, a sensing detector and a communication receiver.The transmitter sent modulated signals to the communication receiver for information transmission.Due to the non-line of sight scattering effect, certain components of the transmitted signals reached the unknown target which further reflected to the sensing detector for target detection.Two performance metrics for communication and sensing were considered, including the mutual information between the transmitted symbol and the signal at the communication receiver, and the miss detection probability for the target detector.The relationship between the two metrics and the transmission parameters was further analyzed, including the transmission power for the high-level signal, the transmission power for the low-level signal, and the prior probabilities.The results demonstrate a tradeoff between the communication performance metric and sensing performance metric.It is also shown that the power for the high-level signal should be set to be the peak power, and the power for the low-level signal and the prior probabilities should be optimized, to minimize the miss detection probability given a lower bound on the mutual information.